PARADOXES AND QUASI-PARADOXES IN ACCOUNTING - Belyaeva, Lyudmila; Peniak, Yuliia; Lukin, Vladimir (European Science, 2023)
Сritical consideration of the category "accounting paradox" and its place in the science of accounting